Who Counts Resilience and Whose Resilience Counts? Applying the Resilience Alliance Workbook - Bartels, Wendy-Lin; Athayde, Simone Ferreira de; Mello, Ricardo; Sobreiro, Thaissa S; Almeida, Juliana de; Bernasconi, Paula; Olival, Alexandre; Simão, Berenice; Silveira, Ruth; Baby, André Luís Torres; et al. (Sustainability in Debate, 2016)
The Brazilian Amazon is a complex social-ecological system, the management of which includes diverse groups of social actors whose values and interests influence decision making and outcomes. Such management requires leaders who appreciate the multiple knowledge systems and historical land occupation trajectories that have shaped this region. Twenty-three emerging leaders from universities, government agencies, the private sector, and social movement organizations participated in a two-year Specialization Course in the state of Mato Grosso, Brazil. Course participants applied the Resilience Assessment (RA) Workbook for Practitioners to analyze three livelihood sub-systems within the municipality of Cotriguaçu. This paper offers reflections on the utility of the RA workbook as a tool for bridging multiple stakeholders’ knowledge, identities, power and interests in collaborative social-ecological management. Our experience points to the risks of conducting expert-led RAs in regions dominated by historical legacies of oppression, weak institutions, and limited governance.